Fire resistance of composite shear walls filled with demolished concrete lumps and self-compacting concrete - Xiong, Yan; Chen, Yaxin; Wu, Bo; Zhao, Guowei (Frontiers in Materials, 2022)
The recycling and reuse of waste concrete is conducive to promoting the sustainable development of resources and practicing the concept of green development. Demolished concrete lumps (DCLs) and self-compacting concrete (SCC) made from waste concrete take full advantage of their recyclability. In order to fully utilize the advantages of demolished concrete lumps and self-compacting concrete in construction, applying demolished concrete lumps and self-compacting concrete to composite shear wall structures is an effective way to reduce costs and improve industrial production. In this paper, a new composite shear wall filled with demolished concrete lumps and self-compacting concrete is proposed, and its fire performance is investigated. The shear wall combines edge constraints of concrete-filled steel tubes, demolished concrete lumps and self-compacting concrete. In order to facilitate the mass pouring of demolished concrete lumps, a cavity is formed between the steel tubes at the ends and the precast walls on both sides. A double-sided fire tests was conducted on three composite shear wall specimens filled with demolished concrete lumps and self-compacting concrete at a constant axial compression ratio, where the fire-retardant coating and the wall width-to-depth ratio were considered as the main test parameters. The specimens were able to steadily withstand the predetermined axial loads during the fire resistance time of 180 min and showed good fire resistance. The concrete temperature variation trends of the three specimens in the wall section were basically the same. The fire-retardant coating on the concealed column had a significant effect on the section temperature of the steel tube, while increasing the wall width-to-depth ratio had little effect. When the axial compression ratio was 0.19, the specimens were in the expansion stage within 180 min and no compression occurred. The results show that the expansion deformation of the shear wall sprayed with fire-retardant coating on the outer surface of the concealed column is smaller than that of the shear wall without fire-retardant coating, and the axial deformation of the composite shear wall infilled with demolished concrete lumps and self-compacting concrete is not affected by increasing the wall width-to-depth ratio.